The Measurements of Tourist Satisfaction Levels on Attractions, Accessibility, and Amenities in Pulesari Tourism Village, Sleman Regency - Muhammad Dzulkifli (Jurnal Pariwisata Terapan, 2020)
This study aimed to determine the level of tourist satisfaction and the performance of attractions, accessibilities, and amenities (3As) in Pulesari Tourism Village (PTV). This study uses both qualitative and quantitative (mixed method). The population in this study was tourists who visited PTV during the period of August to September 2018. A hundred samples were collected using Purposive Sampling method. Data were collected by distributing questionnaires, in-depth interviews, field observations, and documentation. Gradual quantitative-qualitative data analysis is used as a technique to analyse the data. It begins with Likert satisfaction analysis, Importance Performance Analysis, and qualitative descriptive analysis. The results showed that the level of tourist satisfaction was in the satisfied category. Managers need to improve the quality of attraction components and become a priority to meet tourist expectations. Based on this study, the results show that the quality of the 3As component influences the level of satisfaction of visiting tourists. The three components become unity and support each other. A low assessment of one component can be improved by other components that are perceived to have better quality.